Estimating Financial Risk in The Era of Hyper Volatility - Paweł STĘPIEŃ (Communications of International Proceedings, 2022)
The article presents and conditionally evaluates the effectiveness of the currently used risk estimation method based on the VaR method. The author notes that the changes that have taken place in the global economy in the last decade have resulted in an increase in volatility on the markets, both commodity and currency markets. Which directly translates into the level of estimated losses, as well as the cost and sense of hedging your positions.
Keywords: Global Economy; Finance; Commodity And Currency Markets; Risk Management.